Équivalences pénales et solutions de rechange à l’emprisonnement : la métrique pénale implicite des tribunaux criminels - Tremblay, Pierre; Gravel, Sylvie; Cusson, Maurice (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1987)
Sentencing research has generally neglected taking into account how perceptions of the severity of available sanctions affect sentencing behavior. Based on the magnitude estimates of just how severe penalties of different kinds and different amounts criminal courts perceive them to be, this paper identifies the current exchange rates on what Wilkins has called the “punishment market” explains why so many alternatives to imprisonment experiments have backfired, offers a justification for the existing penal repertoire and finds criminal court's severity scales to be socially well grounded.